Deep geothermal single well (DGSW) : Aberdeen Exhibition and Conference Centre : feasibility report for the Low Carbon Infrastructure Transition Programme (LCITP).: Aberdeen Exhibition and Conference Centre : feasibility report for the Low Carbon Infrastructure Transition Programme (LCITP). (2016) - Unknown
No abstract available